Multiple, short protein binding motifs in ORC1 and CDC6 control the initiation of DNA replication - Hossain, Manzar (Mol Cell, 2021)
The initiation of DNA replication involves cell cycle-dependent assembly and disassembly of protein complexes, including the Origin Recognition Complex (ORC) and CDC6 AAA+ ATPases. We report that multiple short linear protein motifs (SLiMs) within intrinsically disordered regions (IDRs) in ORC1 and CDC6 mediate Cyclin-CDK dependent and independent protein-protein interactions, conditional on the cell cycle phase. A domain within the ORC1 IDR is required for interaction between the ORC1 and CDC6 AAA+ domains in G1, whereas the same domain prevents CDC6-ORC1 interaction during mitosis. Then, during late G1, this domain facilitates ORC1 destruction by a SKP2-Cyclin A-CDK2-dependent mechanism. During G1, the CDC6 Cy-motif cooperates with Cyclin E-CDK2 to promote ORC1-CDC6 interactions. The CDC6 IDR regulates self-interaction by ORC1, thereby controlling ORC1 protein levels. Protein Phosphatase 1 binds directly to a SLiM in the ORC1 IDR, causing ORC1 dephosphorylation upon mitotic exit, increasing ORC1 protein and promoting pre-RC assembly.